EVALUASI TINGKAT KEBERHASILAN INSEMINASI BUATAN (IB) DI DESA KLUMPANG KEBUN KECAMATAN HAMPARAN PERAK - Fajar Indra Syahputra; Media Agus Kurniawan (Journal of Innovation Research and Knowledge, 2025)
This study aims to evaluate the success of artificial insemination (AI) in cattle at Desa Klumpang Kebun, Kecamatan Hamparan Perak, and identify the factors that influence it. This study uses survey methods and secondary data analysis to collect information about the characteristics of respondents, including the experience of cattle breeders and insemination technicians. The results show that most cattle breeders have >10 years of experience (42.85%), while the majority of cattle are 3-5 years old (66.66%) with a Body Condition Score (BCS) at value 3 of 87.54% (260 out of 297 heads). Data analysis shows that out of 6 breeds of cattle inseminated, the artificial insemination success parameters measured, namely Service per Conception (S/C) of 1.17, Conception Rate (CR) of 86.86%, and Calving Interval (CI) of 12.5 months, have achieved a satisfactory level of success. The results of this study indicate that artificial insemination can be an effective strategy in improving reproductive efficiency in cattle in the research area. This study also highlights the importance of the role of breeders and insemination technicians in determining the success of artificial insemination. Thus, this study can serve as a reference for the development of more effective and efficient artificial insemination programs in the research area and surrounding areas.